2004
DOI: 10.1111/j.1398-9995.2004.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of local risk factors for children's atopic symptoms in Hanoi, Vietnam

Abstract: These findings are contrary to the "hygiene hypothesis". Recent immunologic and epidemiologic studies refute the inverse association between allergy and TB and may be one explanation for the positive association in this study. The positive association with pig ownership and farming may be because of exposures on farms in a developing country that may be different from exposures in farms of developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
(32 reference statements)
0
7
0
1
Order By: Relevance
“…30,31 One article each was from Singapore 32 and Vietnam. 33 Four studies reported evidence that urban exposure was associated with asthma and allergic symptoms such as rhinitis and conjunctivitis. 30e33 One article reported that urban exposure was associated with increasing asthma severity among children with asthma (OR 2.58, 95% CI 1.16e5.77).…”
Section: Urban Exposure and Chronic Respiratory Diseasementioning
confidence: 99%
“…30,31 One article each was from Singapore 32 and Vietnam. 33 Four studies reported evidence that urban exposure was associated with asthma and allergic symptoms such as rhinitis and conjunctivitis. 30e33 One article reported that urban exposure was associated with increasing asthma severity among children with asthma (OR 2.58, 95% CI 1.16e5.77).…”
Section: Urban Exposure and Chronic Respiratory Diseasementioning
confidence: 99%
“…12 Similarly, a questionnaire-based study in Hanoi, Vietnam, found a positive relationship between allergic conditions and pig ownership. 13 It is possible that the beneficial immune priming of a farm environment is outweighed by the addition of antibiotics to animal feed. Other evidence also suggests an association between antibiotic administration to children early in life and an increased risk of asthma.…”
Section: Evidence For and Against The Hygiene Hypothesismentioning
confidence: 99%
“…20 However, the results of a Vietnam survey (using ISAAC questionnaire with a low response rate) are contrary to it. 21 Regarding breast-feeding, there are studies supporting a positive association (in the case of asthmatic mothers 22 ), others point to a nonlasting protection, 23 and others show a protective effect. 24 The relationship between asthma and obesity in children also has been controversial; some studies found a positive relationship 25,26 and others did not.…”
mentioning
confidence: 96%